Determining the object structure of ecological and economic research and knowledge base for decision support - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2017)
The mathematical model of natural-technogenic objects is substantiated in the article. Natural-technogenic object of research is defined in form of a system model, which includes the economic, ecological and social components and processes system occurring in the selected systems and in their interaction. Basis for introduction systematic analysis methods for consistent problematic environmental safety tasks solution under conditions of uncertainty has been formed. The complex methods system includes entropy theory provisions on the objects state evaluation, the comparator identification method, substantively substantiated for solving complex environment quality assessment problems. An example of ecological state technogenically loaded landscape-geochemical complexes on the proposed methodological support studied in the work. Обґрунтована математична модель об'єктів природно-техногенної природи. Природно-техногенний об'єкт дослідження визначається у вигляді системної моделі, яка включає економічну, екологічну та соціальну складові та систему процесів, що відбуваються у виділених системах та при їх взаємодії. Сформовані основи для впровадження системних методів аналізу для послідовного розв'язання проблемних задач екологічної безпеки в умовах невизначеності. Комплексна система методів включає: положення теорії ентропії з оцінки стану об'єктів, метод компараторної ідентифікації, змістовно обґрунтований для розв'язання задач комплексного оцінювання якості навколишнього природного середовища. Надано приклад дослідження екологічного стану техногенно-навантажених ландшафтно-геохімічних комплексів на основі запропонованого методичного забезпечення. Обоснована математическая модель объектов природно-техногенной природы. Природно-техногенный объект исследования определяется в виде системной модели, включающей экономическую, экологическую и социальную составляющие и систему процессов, происходящих в выделенных системах и при их взаимодействии. Сформированы основы для внедрения системных методов анализа для последовательного решения проблемных задач экологической безопасности в условиях неопределенности. Комплексная система методов включает: положения теории энтропии по оценке состояния объектов, метод компараторной идентификации, содержательно обоснованный для решения задач комплексного оценивания качества окружающей природной среды. Приведен пример исследования экологического состояния техногенно-нагруженных ландшафтно-геохимических комплексов на основе предложенного методического обеспечения.